Reconhecimento e desigualdade: da ética da autenticidade à cultura do novo capitalismo - Fabrício Maciel (Ciências Sociais Unisinos)
This article has as main objective to discuss what the main moral horizon of contemporary societies would be, before which questions about recognition and social inequality should be considered. In order to do so, I first present, in the introduction, the way in which the concepts of recognition and inequality arise in the current academic scene, pointing to their importance, limits and possibilities of ramifications. Next, I try to show how Charles Taylor outlines, especially in his book The Ethics of Authenticity (2011), in which he rewrites some central theses of his great work The Sources of Self (1997), a moral ideal of modern culture, which is mainly synthesized in the concept of authenticity and which would not have been fulfilled to the fullest. So, I try to analyze how the flexible culture of the new capitalism, schematized by Richard Sennett, mainly in his books The corrosion of character (2006) and The culture of the new capitalism (2015), may be the main contemporary distortion of the Western culture of authenticity. In the final part, I try to show how the culture of this new capitalism becomes a fake moral horizon, by promising a path to self-fulfillment and recognition that is false. With this, this fake moral horizon, perceived in Sennett’s work, suppresses and hides the greatest moral horizon of modernity, which, for Taylor, is explained by the need to search for authenticity, as a synonym of self-fulfillment. Thus, this culture of new capitalism builds and naturalizes modern social inequality even more effectively than in earlier periods.